Motivationen und Resultate der Anti-Konsum Praxis "Stooping"; Motivations and outcomes of the anti-consumption practice "stooping" - Leonie Böhm (Junior Management Science (JUMS), 2024)
Die Klimakrise des 21. Jahrhunderts fordert neue und nachhaltige Formen des alternativen Konsums. Im Rahmen dieser Bachelorarbeit wird die aufstrebende Anti-Konsum Praxis Stooping, eine Art des Second-Hand Konsums, bei dem Gegenstände von Konsumierenden an die Straße gestellt und von anderen kostenfrei konsumiert werden können, erstmals untersucht. Das Ziel dieser Arbeit ist, mögliche Motivationen und Resultate des Stooping zu erforschen. Diese werden aus der existierenden Literatur zu Second-Hand- und Anti-Konsum herausgearbeitet und anschließend mithilfe qualitativer Interviews überprüft. Die Ergebnisse zeigen, dass ökonomische Motive, hedonistische Werte, die Einfachheit der Konsumentscheidungen, Nachhaltigkeitsüberlegungen, das Aufwerten von gefundenen Produkten und eine gute Qualität gebrauchter Produkte Motivationen für Stooping darstellen können. Resultate des Stooping können eine verstärkte Verbundenheit zwischen Verkäufer*in und Käufer*in, zum Objekt sowie eine positive soziale Wahrnehmung der Konsumierenden sein. Die Untersuchung neuer Konsumtrends wie Stooping führt zu einem besseren Verständnis nachhaltiger Konsumpraktiken und kann dazu beitragen, diese als bewusste und geplante Konsum-Alternative zu positionieren. – – The climate crisis of the 21st century demands new and sustainable forms of alternative consumption. Within the scope of this bachelor thesis, the emerging anti-consumption practice of "Stooping", a form of second-hand consumption where items are placed on the street by consumers and can be freely taken and used by others, is examined for the first time. The aim of this paper is to explore possible motivations and outcomes of Stooping. These aspects are extracted from the existing literature on second-hand and anti-consumption and subsequently investigated through qualitative interviews. The results indicate that economic motives, hedonistic values, the simplicity of consumption decisions, sustainability considerations, the upcycling of found products, and the good quality of used products can serve as motivations for Stooping. Outcomes include an increased connection between the seller and the buyer, an increased connection between the buyer and the product, as well as a positive social perception of the consumers. Investigating new consumption trends like Stooping contributes to a better understanding of sustainable consumption practices and can help position them as conscious and deliberate alternatives to traditional consumption.
Keywords: 650; alternative consumption; anti-consumption; second-hand consumption; stooping